Estrógenos na bacia hidrográfica Tietê-Jacaré: ocorrência e avaliação do impacto ambiental - Bezerra, Débora Santos Silva [UNESP] (2014)
Natural and synthetic estrogens are emerging microcontaminants daily released to the environment, included in class of substances that may affect health, growth and reproduction of aquatic organisms and humans, the endocrine disrupters. Occurrence of estrogens has been researched in surface water and suspended particulate matter (SPM) in two important aquifers inserted into the Comitê da Bacia Hidrográfica Tietê-Jacaré (UGRHI 13 - Tietê/Jacaré) , effluent untrated (Bauru River) or treated (Ribeirão das Cruzes) receivers, employing solid phase extraction (SPE) for water , solid-liquid extraction for MPS and QuEChERS for sediments developed reliable analytical criteria (accuracy, precision, selectivity, robustness and evaluation of matrix effect) followed by simultaneous analysis HPLC-FLD-UV in isocratic elution (60:40 MeCN:H2O both 0.1% H3CCOOH) and C18 analytical column. Methods detection and quantification limits were established for FLD and UV detectors. It ranged from 0.009 - 1200 ng mL-1 and 0.03 - 1700 ng mL-1 (FLD) and 0.4 - 1.8 mg mL-1 and 0.6 - 2.6 mg mL-1 (UV) to surface waters; from 1.0 - 28.5 ng g-1 and 1.6 - 42.7 ng g-1 (FLD) for sediment and 290 - 430 ng g-1 and 450 - 630 ng g-1 (FLD) and 90 - 160 ng g-1 and 130 - 230 ng g-1 (UV) for MPS. Recoveries of every method ranged from 60 - 139 % with relative standard deviations 0.5 - 20%. The estrogens partition in aquatic compartments was otherwise for rivers and highest compounds concentrations were found in Bauru River aqueous phase (0.02 - 17 ng mL-1) and suspended solids (791.8 - 14403.8 ng g-1). The samples were submitted to in vivo (biotransformation enzymes and antioxidants defenses) and in vitro (RYA) assays in order evaluate toxicity and environmental impact. All samples showed estrogenic activity with EEQ ranged from 1.0 - 880.0 nM in the RYA for surface water and 0.4 - 56.7 nM for MPS. Additionally, changes has been observed in phase Ι and ΙΙ besides...